A phase II trial to evaluate the efficacy of fostamatinib in patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). (February 2016) - Flinn, Ian W.; Bartlett, Nancy L.; Blum, Kristie A.; Ardeshna, Kirit M.; LaCasce, Ann S.; Flowers, Christopher R.; Shustov, Andrei R.; Thress, Kenneth S.; Mitchell, Patrick; Zheng, Fred; Skolnik, Jeffrey M.; Friedberg, Jonathan W.
Abstract: Purpose: To assess the safety and efficacy of fostamatinib in patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). Experimental design: Relapsed or refractory DLBCL patients originally received the oral spleen tyrosine kinase inhibitor, fostamatinib in a two-arm, randomised, double-blinded manner at either 100 mg twice a day (BID) or 200 mg BID until disease progression or unacceptable toxicity. The primary objective was to assess the overall response rate (ORR). Preliminary analysis showed limited efficacy and all subsequent patients were treated at 200 mg BID. Previously randomised patients were unblinded and given the opportunity to receive 200 mg BID. Results: Sixty-eight patients were treated (47 at 200 mg BID, 21 at 100 mg BID). Cell of origin analysis showed 58% germinal B-cell (GCB) origin, 30% activated B-cell (ABC) origin and 12% with an intermediate cell of origin signature. The most common treatment-related adverse events of all patients were diarrhoea (21% total, 6% grade 3/4), nausea (19% total, 3% grade 3/4), and, fatigue (18% total, 9% grade 3/4). The ORR rate was 3% across both arms and clinical benefit (≥stable disease) was achieved for 13% of all patients. The cell of origin for patients with clinical benefit was GCB (4 patients), intermediate (4 patients) or unknown (1 patient). None of the patients with clinical benefit had ABC genotype. Conclusions: While fostamatinib was generally well tolerated in this patient population, efficacy at these doses and schedule was poor. Unlike data with other B-cell antigen receptor pathway inhibitors, responses were not observed in the ABC genotype. Highlights: Fostamatinib was well tolerated in patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). Fostamatinib was poorly effective in patients with relapsed or refractory DLBCL. Fostamatinib clinically benefited patients with germinal B-cell or intermediate cell of origin. This work helps refine the appropriate treatment regimen for patients with DLBCL.